Sistem Informasi Kerentanan Gizi Buruk di Distrik Sentani, Kabupaten Jayapura dengan Metode Analytic Hierarchy Process - Yokelin Tokoro; Dharmaputra Palekahelu; Andeka Rocky Tanaamah (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2013)
This study is aimed to determine the vulnerability of malnutrition in every village of SentaniDistrict by analyzing the factors of malnutrition acording to UNICEF standard usingAnalytical Hierarchy Proses method. These factors include nutrition, infectious diseases,parenting, food availability, sanitation, and poverty. These factors are known as the criteria inthe AHP process that use to determine the preferred alternative (the village) which isvulnerable to malnutrition. The result of this study can be used as a Decision SupportSystem (DSS) to help the stakeholders in addressing the malnutrition problems on the righttarget by pressing the factors